Proceedings of the 19th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2013
DOI: 10.1145/2487575.2487713
|View full text |Cite
|
Sign up to set email alerts
|

A tool for collecting provenance data in social media

Abstract: In recent years, social media sites have provided a large amount of information. Recipients of such information need mechanisms to know more about the received information, including the provenance. Previous research has shown that some attributes related to the received information provide additional context, so that a recipient can assess the amount of value, trust, and validity to be placed in the received information. Personal attributes of a user, including name, location, education, ethnicity, gender, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…As a preliminary study, I designed a novel web based tool [34] for collecting attribute values of interest associated with a particular social media user. I refer to these attributes as Provenance Attributes and the tool as Provenance Data Collector.…”
Section: User's Vulnerability Across Platformsmentioning
confidence: 99%
“…As a preliminary study, I designed a novel web based tool [34] for collecting attribute values of interest associated with a particular social media user. I refer to these attributes as Provenance Attributes and the tool as Provenance Data Collector.…”
Section: User's Vulnerability Across Platformsmentioning
confidence: 99%
“…Another line of research [2,8] has shown that many attributes of a user, called as Provenance Attributes, can be collected from social media. Provenance attributes of a user may include name, location, gender, occupation, and political and religious affiliations.…”
Section: Related Workmentioning
confidence: 99%
“…The meta information such as the list of tweets and users are also given. Using this information, users can find the most active propagators of the information and their provenance information such as political affiliation and interests using tools proposed in [4]. For example, the account of one of the most active users, 16, leans very strongly towards hardline nationalism.…”
Section: Demonstrationmentioning
confidence: 99%
“…Provenance Attributes relates to the qualification and affiliation of the users along the path, giving an idea about their relevance and reliability for a given piece of information. A tool to seek provenance attribute information is presented in [4]. Provenance Path relates to the origins, custody chain and the ownership of the information, enabling the user to assess the reliability of the source, the relation between the origin and ownership and the users influencing information propagation.…”
Section: Introductionmentioning
confidence: 99%